Mitigating Routing Misbehavior in Disruption Tolerant Networks - Devadharshini, S; Vadivel, R (International Journal of Computer Sciences and Engineering, 2022)
Destructive Tolerance Network (DTN) can drop packets received by selfish or malicious nodes. These routing malfunctions slow down packet delivery and waste system resources such as power and bandwidth. Techniques have been proposed to mitigate routing malfunctions in mobile ad hoc networks, but they cannot be applied directly to DTN due to the intermittent connections between the nodes. To address this issue, we propose a distributed method to detect packet drops on the DTN. In our scheme, the node should keep a signed contact record for the previous contact. Based on this, the next node to contact can determine if the node dropped the packet. Rogue nodes can falsely report contact records to avoid detection, so a small portion of each contact record is distributed to the specified number of watch nodes and the appropriate contact record. Can be collected to identify rogue nodes. We also propose a scheme to mitigate incorrect routing behavior by limiting the number of packets forwarded to malicious nodes. Trace-based simulations show that our solution is efficient and can effectively mitigate routing fraud.